Sex Education for high school students: perceptions, gaps and possibilities (Research, Society and Development, 2022)
Unprotected sexual practice is the main cause of the increase in the incidence of Sexually Transmitted Infections in young people (STIs) and is related to the early onset of sexual life. Sex education and obtaining correct and safe information for young people is essential for citizenship education. Thus, the present work aimed to evaluate the knowledge of high school students about STIs and the results of a didactic intervention on the subject. To this end, 158 students from public high schools in the interior of the state of Goiás participated in the study, which involved filling in a pre-test questionnaire, carrying out a didactic intervention and completing a post-test questionnaire. Students believe in misinformation regarding the transmission of STIs and consider the school as the main agent responsible for sex education. However, students use the internet as the main source to search for information on issues related to sexuality. Thus, the present work highlights the importance of the role of the school and of didactic interventions related to sexuality for the prevention of STIs, teenage pregnancy and for the formation of more responsible and autonomous young people.